High prevalence of hepatitis C infection in a Brazilian prison: identification of risk factors for infection - Guimarães,Thaís (2001)
Hepatitis C virus (HCV) causes infectious hepatitis worldwide. It is transmitted mainly by blood products and sharing of intravenous paraphernalia during illicit drug use. High prevalence rates have been described among specific groups considered to be at higher risk for HCV infection, including prison inmates. The objectives of this study were: to determine the HCV seroprevalence among inmates of Casa de Detenção de São Paulo; to identify risk factors for HCV infection; and to compare the seroprevalence of HCV to other blood borne or sexually transmitted diseases. From December, 1993, to January, 1994, a total of 779 inmates were interviewed to collect information on sociodemographic status, sexual behavior, and past experience with illicit drugs. Blood samples were obtained from 756 inmates for serological tests. 310 (41%) blood samples were positive for anti-HCV, 425 (56.2%) were negative, and 21 (2.8%) showed indeterminate results. In this population, we found a seroprevalence of 13.7% for HIV, 3.3% for syphilis (VDRL), and 68.1% for hepatitis B virus previous infection. Four variables were each identified as associated with a positive anti-HCV serologic test: a positive VDRL (OR = 2.63 IC 95% 1.08 to 6.36); a time of current imprisonment longer than 130 months (OR = 2.44 IC 95% 1.04 to 5.71); previous incarceration at Casa de Detenção de São Paulo (OR = 1.73 IC 95% 1.19 to 2.52) and; illicit drug use before admission to the Casa de Detenção de São Paulo (OR = 1.64 IC 95% 1.15 to 2.33). The seroprevalence of HCV antibodies among the study population was high (41%), indeed, one of the highest clusters of HCV infection recorded until now. Four variables were each shown to be associated with HCV infection. The simultaneous presence of these 4 variables is associated with an 82% probability of being anti-HCV positive. Although risk factor analysis indicates most HCV infections occur prior to inprisonment, initiation of control measures to prevent continued transmission after incarceration should be done.